Ocular Pulse Amplitude Measurement Using Pascal Dynamic Contour Tonometer in Glaucoma Patients - Katsimpris, J. M.; Theoulakis, P. E.; Papadopoulos, G. E.; Katsimpris, A.; Lepidas, J.; Petropoulos, I. K. (Klinische Monatsblätter für Augenheilkunde, 2014)
Aim: This study aims to measure and compare the ocular pulse amplitude using Pascal dynamic contour tonometry in normal persons and in glaucoma patients.Patients and Methods: 20 patients (40 eyes) with primary open angle glaucoma (Group A), 8 patients (16 eyes) with normal tension glaucoma (Group B), and 12 patients (24 eyes) with ocular hypertension (Group C) were included in the study. Control group (Group D) comprised 25 normal volunteers (50 eyes). Intraocular pressure was measured using both Goldmann applanation tonometry in the slit–lamp and Pascal dynamic contour tonometry. Ocular pulse amplitude was evaluated with Pascal dynamic contour tonometry. Statistical evaluation of the differences in ocular pulse amplitude and intraocular pressure among the different groups was performed using Studentʼs t-test.Results: Mean ocular pulse amplitude values expressed in mmHg were 3.66 ± 1.00, 2.46 ± 0.60, 4.04 ± 1.47, and 2.52 ± 0.52, for Groups A, B, C, and D, respectively. The ocular pulse amplitude was significantly higher in Group A (primary open angle glaucoma) and Group C (ocular hypertension) when compared with Group D (control group) and Group B (normal tension glaucoma). No statistically significant difference was detected between Group D (control group) and Group B (normal tension glaucoma).Conclusions: Although we can measure the intraocular pressure with Goldmann applanation tonometry, no information can be derived regarding the ocular pulse amplitude. The use of Pascal dynamic contour tonometry in intraocular pressure estimation provides useful clinical information also about the magnitude of the ocular pulse amplitude in different types of glaucoma. Pascal dynamic contour tonometry discloses an elevation of ocular pulse amplitude in primary open angle glaucoma and ocular hypertension patients. On the contrary, the ocular pulse amplitude is within normal limits in normal tension glaucoma patients.
Keywords: ocular pulse amplitude; glaucoma; dynamic contour tonometry